2011
DOI: 10.4274/mirt.21
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m HIG Scintigraphy in Detection of Active Inflammation in Ankylosing Spondylitis

Abstract: Objective: The diagnosis of active inflammation in ankylosing spondylitis (AS) is crucial for treatment to delay possible persistent deformities. There are no specific laboratory tests and imaging methods to clarify the active disease. We evaluated the value of Tc-99m human immunoglobulin (HIG) scintigraphy in detection of active inflammation. Material and Methods: Twenty-nine patients were included. Tc-99m methylenediphosphonate bone (MDP) and HIG scintigraphies were performed within 2-5 day intervals. Two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…6 Skeletal scintigraphy (bone scan) has also been found to be sensitive in detecting active disease in the SI joints, although unhelpful in the diagnosis of inactive AS. 7 Magnetic resonance imaging has accuracy in diagnosing early-stage AS inflammatory lesions in the spine and SI joints using fluid-sensitive sequences with fat saturation and contrast enhancement. 6,8 Hoffstetter et al found that lesions revealed on MRI were most likely to occur in the SI joints and spine (62%) and least likely to occur in the spine alone (10%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Skeletal scintigraphy (bone scan) has also been found to be sensitive in detecting active disease in the SI joints, although unhelpful in the diagnosis of inactive AS. 7 Magnetic resonance imaging has accuracy in diagnosing early-stage AS inflammatory lesions in the spine and SI joints using fluid-sensitive sequences with fat saturation and contrast enhancement. 6,8 Hoffstetter et al found that lesions revealed on MRI were most likely to occur in the SI joints and spine (62%) and least likely to occur in the spine alone (10%).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic ultrasound (US), magnetic resonance imaging (MRI), bone scintigraphy, and dual-energy x-ray absorptiometry may be used to aid in the diagnosis or gauge treatment effectiveness. [4][5][6][7][8][9][10][11][12] Biomarkers are utilized in the workup of AS. Human leukocyte antigen B27 (HLA-B27) (90%-95%) and endoplasmic reticulum aminopeptidase 2 (ERAP2) are a few genetic markers.…”
Section: Introductionmentioning
confidence: 99%
“…Few pilot studies reported the use of immunoscintigraphy with radiolabeled human immunoglobulin or anti-TNF-α in the detection of active sacroiliitis in patients with axSpA. Their results suggest that immunoscintigraphy may have value in the diagnosis of active sacroiliitis ( 90 92 ). Lacking confirmation in longitudinal studies, scintigraphy with radiolabeled anti-TNF-α may display good correlation with MRI findings and biological treatment response ( 92 ).…”
Section: Radionuclide Methodsmentioning
confidence: 99%
“…Polyclonal human immunoglobulin (HIG) scintigraphy has been proposed as a reliable and objective imaging method for joint inflammation [16,17]. The mechanism of HIG accumulation in the site of inflammation is not clear [18,19]. The following hypotheses have been proposed for the mechanism: increased vascular permeability [20], specific capture of IgG by receptors for immunoglobulins in inflammatory cells [21], binding to extracellular matrix proteins [22] and bacterial affinity [23].…”
Section: Introductionmentioning
confidence: 99%